Responder Threshold for Patient-Oriented Eczema Measure (POEM) and Children's Dermatology Life Quality Index (CDLQI) in Adolescents with Atopic Dermatitis - Eric L. Simpson; Marjolein de Bruin-Weller; Laurent Eckert; Diane Whalley; Isabelle Guillemin; Matthew Reaney; Zhen Chen; Lauren Nelson; Shanshan Qin; Ashish Bansal; Abhijit Gadkari (Adis, Springer Healthcare, 2019)
Abstract Introduction The Patient-Oriented Eczema Measure (POEM) assesses patient-reported frequency of atopic dermatitis (AD) symptoms, while the Children's Dermatology Life Quality Index (CDLQI) measures the impact of skin disease on health-related quality of life (HRQoL) in children. There is currently no threshold for clinically meaningful within-person change in POEM or CDLQI scores in adolescents. Here we empirically derive within-person thresholds of meaningful within-person change in POEM and CDLQI scores in adolescents with moderate-to-severe AD. Methods Data were used from a phase 3, randomized, double-blind, placebo-controlled trial of dupilumab in adolescents (aged ≥ 12 to < 18 years) with moderate-to-severe AD. Anchor-based methods were employed using the mean change in POEM and CDLQI scores from baseline to week 16 linked with a 1-point improvement in Patient Global Assessment of Disease (PGAD), a score of "a little better" on the Patient Global Assessment of Treatment effect (PGAT), a 50-74% improvement from baseline in the Eczema Area and Severity Index (EASI-50-74), and a 1-point improvement in Investigator's Global Assessment (IGA) score. Results A mean change of − 7.8 and − 5.6 in the POEM score was associated with PGAD and PGAT anchors, respectively. EASI-50-74 was associated with a mean change in POEM score of − 8.2, while the IGA anchor was associated with a mean change of − 7.9 in POEM score. The mean changes in CDLQI score associated with PGAD and PGAT anchors were − 6.4 and − 6.6, respectively, while CDLQI mean scores changed by − 8.3 and − 8.0 for the EASI and IGA anchors, respectively. Conclusion In adolescents (aged ≥ 12 to < 18 years) with moderate-to-severe AD, a within-person change of 6-8 points in POEM and CDLQI scores, independently, can be considered a reasonable responder threshold for clinically meaningful change in each of the two scales, respectively. Trial Registration ClinicalTrials.gov Identifier: NCT03054428. Funding Sanofi and Regeneron Pharmaceuticals, Inc.